Evaluation of sources and rates of P fertilizers on the initial growth of corn - Harger, Nelson; Brito, Osmar R.; Ralisch, Ricardo; Ortiz, Fábio Rogério; Watanabe, Toshio Sérgio (Semina: Ciências Agrárias, 2007)
Phosphorus is an essential element for all living organisms and important also for agricultural production. The content of P in most agricultural soils in Brazil is low. In order to supply the plant needs and the soil fixation, application of P fertilizer is required. Among the various options of P fertilizers in the market, the totally acidified phosphates are usually commercialized. The evaluation of the efficiency of the reactive natural phosphates as P fertilizers is important due to the increase of the utilization of cheaper sources of natural P. The experiment was carried out in green house, using a Nitossolo. The experimental design used was complete randomized design, with the treatments in a 4x2 factorial arrangement, and four replications. The objective of the experiment was to evaluate the effects of sources and rates of P on the growth of corn. The production of dry matter and the content of P on the corn leave and stalks (above ground corn parts) increased as rates of P increased, regardless the P sources tested. However, the Triple Super Phosphate was more efficient compared with Arad phosphate, providing better nutrition and initial growth of corn plants.